2021
DOI: 10.1186/s12940-021-00694-2
|View full text |Cite
|
Sign up to set email alerts
|

Houston hurricane Harvey health (Houston-3H) study: assessment of allergic symptoms and stress after hurricane Harvey flooding

Abstract: Background In August 2017, Hurricane Harvey caused unprecedented flooding across the greater Houston area. Given the potential for widespread flood-related exposures, including mold and sewage, and the emotional and mental toll caused by the flooding, we sought to evaluate the short- and long-term impact of flood-related exposures on the health of Houstonians. Our objectives were to assess the association of flood-related exposures with allergic symptoms and stress among Houston-area residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Studies on the health effects of flooding events in the USA have been conflicting, and while there is a general trend towards a link between atopic disease and fungal exposure, at least in children, this is not clearcut and is not often related to risk of IgE sensitisation. [42][43][44]…”
Section: Dovepressmentioning
confidence: 99%
“…Studies on the health effects of flooding events in the USA have been conflicting, and while there is a general trend towards a link between atopic disease and fungal exposure, at least in children, this is not clearcut and is not often related to risk of IgE sensitisation. [42][43][44]…”
Section: Dovepressmentioning
confidence: 99%
“…Health impacts from flooding can be physical or psychological. Physical outcomes include gastrointestinal illnesses, respiratory illnesses, skin rashes and infections and poisoning from exposure to chemical irritants [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Psychological distress and trauma are common among people who have experienced sudden flooding as a result of extreme weather events [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following Houston hurricane a survey was conducted which explored allergy and stress in the affected population. Results suggested that the affected population showed higher rate of allergies and high stress score (14). However association with cancer or longer follow-up of the population was not done as part of the study.…”
Section: % Of Patients Experiencedmentioning
confidence: 97%